A low cost smart power meter for IoT. (March 2019) - Abate, F.; Carratù, M.; Liguori, C.; Paciello, V.
Highlights: Internet of Things requires interconnected monitoring and actuating devices. Widespread dissemination of meters is crucial. IoT Smart Meter fundamental features are communication, low cost and accuracy. Monitoring electrical consumption with low cost device without losing accuracy. Abstract: The smart city in urban planning and architecture is a set of urban planning strategies aimed at optimizing and innovating public services so as to relate the material infrastructures of cities "with the human, intellectual and social capital of those who live there" thanks to the widespread use of new communication technologies, mobility, environment and energy efficiency, in order to improve the quality of life and meet the needs of citizens, businesses and institutions. Nowadays we hear more and more about the Internet of Things (IoT). Smart devices connected to the internet are increasing in cities. Cities become smart, but at the same time it is not considered the quality of data that these devices send over the internet. The authors, starting from the experience gained previously, in this work focus on energy efficiency, and in particular how energy measurements are performed and sent. The authors propose a low cost smart electric meter for the measurement of electrical parameters. The meter is capable of adapting to the variability of the grid maintaining a high level of measurement accuracy. On the proposed smart meter two algorithms are developed and compared both in simulation and with real signals.